Charinus bromeliaea sp. n. (Amblypygi: Charinidae); a new species of bromeliad inhabiting whip spider from French Guyana - Jocque, Merlijn; de Leão Giupponi, Alessandro Ponce (Zootaxa, 2012)
A new species of Charinus Simon, 1892 is described from French Guyana, raising the number of species in the genus to48 (27 for the Neotropical region and 19 for South America). Charinus bromeliaea sp. n. is distinguished from the otherspecies in the genus by morphological characteristics and unique ecology. Adapted to live in Achmea bromeliads on gran-ite inselbergs, this species is an interesting addition to the wide range of habitats Charinus species are found in. This is also the first record of the genus from French Guyana and this record extends the geographic distribution of the genus.